The impact mechanism of China's green finance on the transformation and innovation of high-energy-consumption enterprises. - Weimin Xiang; Yeqiang Lan; Qiao Qi; Lei Gan (PLoS ONE)
The development of green finance and the promotion of green transformation and upgrading of high energy-consuming enterprises are of great significance for China to achieve the "double carbon" goal. This paper employs a dual fixed-effects model to examine the profound ramifications and intrinsic mechanisms of green finance development on the transformative innovation of high-energy-consumption enterprises, using a sample of 462 publicly traded high-energy-consuming corporations from the period spanning 2016 to 2020. The results show that the development of green finance promotes the transformation and innovation of energy-intensive enterprises and that market-incentivized environmental regulation plays a partially mediating role; the results of heterogeneity analysis show that green finance promotes the transformation and innovation of high energy-consuming enterprises with significant differences in different low-carbon pilot regions, company ownership, and enterprise size; the mechanism analysis shows that the development of green finance can increase government subsidies and alleviate financing constraints to promote the transformation and innovation of high energy-consuming enterprises; it is also found that the development of green finance can significantly improve the financial performance of enterprises. The research findings of this paper hold significant implications for promoting the sustainable development of green finance and high-energy consumption enterprises in China. They provide valuable insights and references for facilitating the green transformation and innovation of high-energy-consuming enterprises in China as well as other developing countries.